The emergence of the emergence-based approach in community practice. Issue 2 (3rd April 2019) - Shemer, Orna; Agmon-Snir, Hagai
ABSTRACT: Community practitioners are often challenged to work in complex environments and situations that naturally occur in communities. This article focuses on the theoretical and practical use of the Emergence-Based Approach that is relevant for work in complex community situations. Using this approach, the practitioner encourages the emergence of novel ideas and initiatives, and engages a decentralized network of activists, helping them develop their initiatives. Using a field study, we compare this approach to the traditional Outcomes-Based Approach. Although their mindsets are very different, and even contradict one another, we suggest practical ways to combine the two in an effective way.